Chemical composition and sensory analysis of fresh pineapple juice and deacidified pineapple juice using electrodialysis - 312737 Masniza Sairi; Law, Jeng Yih; Mohamad Roji Sarmidi; Regional Symposium on Membrane Science and Technology (2004 : Johor Bahru) (Skudai Universiti Teknologi Malaysia, 2004)
50